Assessment of CO2 Levels Prior to Injection Across the Quest Sequestration Lease Area. (July 2017) - Rock, Luc; McNaughton, Cameron; Black, Andy; Nesic, Zoran; Whiticar, Michael; Grant, Nick; Jassal, Rachhpal; Lahvis, Matthew; Davies, Christian; DeVaull, George; Shevalier, Maurice; Nightingale, Michael; et al.
Abstract: The Quest Carbon Capture and Storage (CCS) project in Alberta, Canada, is a fully integrated project, as it involves the capture, transport, injection, storage of CO2, and a measurement, monitoring and verification (MMV) program. The MMV program has two key objectives: a) to ensure containment and b) to ensure conformance. Prior to the start of CO2 injection at the end of August 2015, a number of projects were undertaken to gather data from various domains, namely the atmosphere, biosphere, hydrosphere and geosphere, to provide input to the Quest MMV program. The focus of this paper is on monitoring activities undertaken in relation to the atmosphere and biosphere domains. Activities undertaken across the Quest sequestration lease area (SLA) included an eddy covariance system, soil gas probes, soil flux chambers, and walk-over surveys. In conclusion, understanding the spatial and temporal variability of CO2 levels prior to start of CO2 injection represents an important activity of a CCS MMV program. It provides technical input to the development of such a program, but also provides knowledge for communication to and awareness of project stakeholders (e.g. landowners) regarding CO2 levels within the atmosphere and biosphere across a SLA.